Master Drawings. (New York City : The Master Drawings Association, 1963)
In publication since 1963, Master Drawings is a quarterly devoted to the study and illustration of Western draftsmanship from the fourteenth through the twentieth centuries. It deals with all aspects of the field, including the publication of unknown material and new attributions, as well as the presentation of significant findings regarding the collecting, function, subject matter, and conservation of drawings. Typical issues include articles and reviews of books and exhibition publications by scholars from throughout the Americas and Europe. The language of the quarterly is English. An annual index is issued in the fourth number of the respective volume and a comprehensive index, updated annually, is accessible at www.masterdrawings.org. (Jstor)
Www.masterdrawings.org
Online: https://www.jstor.org/journal/masterdrawings
Engels
Tijdschriften
Keywords: tekeningen